ChemInform Abstract: Gallium Trichloride Catalyzed Hydroamination of Alkynes: Scope, Limitation, and Mechanistic Studies by DFT. Issue 11 (8th March 2013) - Li, Lei; Huang, Genping; Chen, Zhou; Liu, Wei; Wang, Xiufang; Chen, Yanmei; Yang, Lijuan; Li, Wu; Li, Yahong
Abstract This reaction predominantly gives the Markovnikov hydroamination products.